2000
DOI: 10.1097/00007890-200006150-00034
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Outcome of Living Donors for Adult to Adult Right Lobe Transplantation

Abstract: Donor selection limits the application of living donor liver transplantation in the adult population. Unrelated individuals increase the size of the donor pool. Right lobe hepatectomy can be performed safely in healthy adult liver donors. Preoperative liver biopsy is an essential part of the evaluation protocol, particularly when the estimated graft mass is marginal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
148
2
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(159 citation statements)
references
References 24 publications
1
148
2
8
Order By: Relevance
“…The prevalence of histologically-defined NAFLD was 20% and 51% in two different studies comprised of potential living liver donors. 12,13 The reported prevalence of NAFLD when defined by liver ultrasound ranged between 17% and 46% depending on the population studied. 4 In a study consisting of nearly 400 middle aged individuals, the prevalence of NAFLD defined by ultrasonography was 46% and the prevalence of histologically confirmed NASH was 12.2%.…”
Section: Incidence and Prevalence In The General Populationmentioning
confidence: 99%
“…The prevalence of histologically-defined NAFLD was 20% and 51% in two different studies comprised of potential living liver donors. 12,13 The reported prevalence of NAFLD when defined by liver ultrasound ranged between 17% and 46% depending on the population studied. 4 In a study consisting of nearly 400 middle aged individuals, the prevalence of NAFLD defined by ultrasonography was 46% and the prevalence of histologically confirmed NASH was 12.2%.…”
Section: Incidence and Prevalence In The General Populationmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15] It is difficult to quantify the true incidence of NAFLD because of the variation in diagnosis and also due to the fact that a large number of patients may be asymptomatic. Nevertheless, a review of literature showed that the reported incidence of NAFLD varies…”
Section: Incidence and Prevalence Of Non-alcoholic Fatty Liver Diseasmentioning
confidence: 99%
“…9 In the USA, a study of living donors for adult to adult right lobe LT candidates that were biopsied showed that 20% of them were ineligible due to > 30% steatosis on biopsy samples. 10 It is accepted that the prevalence of NAFLD varies greatly based on the population studied and based on the screening test such as liver enzymes, liver histology, or imaging. 11 In high-risk groups with metabolic syndrome or surrogates of diabetes, obesity, and dyslipidemia, there is a significantly higher prevalence in contrast to lower rates in unselected groups.…”
Section: Incidence and Prevalence Of Non-alcoholic Fatty Liver Diseasmentioning
confidence: 99%
“…This course may necessitate alteration of the routine sequence of vascular anastomoses during transplantation such that the arterial anastomosis is performed before the portal venous anastomosis. 36 Depiction of the arterial supply to segment IV, which arises from the right hepatic artery in approximately 11% of patients, is very important because preservation of the vascular supply to segment IV is mandatory to ensure function of this segment in the donor 7,37 (Fig. 5).…”
Section: S10mentioning
confidence: 99%
“…6 Recent improvements in surgical technique have permitted the safe performance of right hepatectomy for transplantation, thereby allowing adults awaiting transplants to benefit from living-related donors. 7 However, given the far greater complexity of right hepatectomy, safe harvesting and successful transplantation requires careful selection of donors.…”
mentioning
confidence: 99%